Diversity and Exclusivity - M. Ashraf Adeel (International Institute of Islamic Thought, 2009)
It is argued that religions seem to insist, paradoxically, on both exclusivity and diversity to inspire passionate commitment on the one hand and to allow for genuine choice of religion on the other. The argument is developed with special reference to Islam, with hints of similar strands of thought in Judaism and Christianity. The paradoxicality of this position of religions is similar to Kierkegaard’s interpretation of faith, as exhibited byAbraham in his sacrifice. Interpreting religions in this way provides us with a better context for understanding the exclusivism/pluralism debate.